Monopoly and Its Varieties: Conceptual Framework for Economic Governance in Law - Chęciński, Remigiusz (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2024)
The article explores the concept of monopoly from legal and economic perspectives, and aims to develop a unified analytical framework for assessing monopolistic structures within economic governance systems. The author categorizes monopolies into three types: factual, natural, and legal, analysing their features and interrelations in the context of European and Polish law. Special attention is given to the interaction between legal regulations and economic realities, proposing that the notion of a “monopoly system” integrates these categories. The article provides a conceptual framework aligned with EU law principles, emphasizing the need for compliance with proportionality and internal market rules. Examples from Polish law, such as the currency monopoly and the organization of sports competitions, illustrate the discussion.